Relationship between changes in serum keratin 18 and changes in liver histology in children and adults with nonalcoholic fatty liver disease - Vuppalanchi, Raj (Clin Gastroenterol Hepatol, 2014)
BACKGROUND & AIMS: Previous cross-sectional studies have shown that serum keratin 18 (K18) fragment levels predict liver histology in individuals with nonalcoholic fatty liver disease (NAFLD). We conducted a study to examine the relationship between changes in serum K18 levels and changes in liver histology in both adults and children with NAFLD. METHODS: Serum K18 levels were measured at baseline and at various time points in 231 adults and 152 children with NAFLD who participated in two randomized controlled trials. Liver biopsies from baseline and week 96 were reviewed centrally. RESULTS: There was greater decrease in serum K18 levels in adults with histological improvement at week 96 than those without histological improvement at week 16 (-193 ± 293 vs -139 ± 467 U/L, p<0.001), week 48 (-232 ± 360 vs -113 ± 425 U/L, p<0.001), and week 96 (-269 ± 368 vs -97 ± 400 U/L, p<0.001). There was greater decrease in serum K18 levels in children with histological improvement than those without histological improvement at week 48 (-197 ± 467 vs.-47 ± 350 U/L, p=0.005) and week 96 (-206 ± 432 vs. -2 ± 474 U/L, p<0.001). However, decrease in serum K18 was not better than decrease in ALT in identifying histological improvement in adults (AUROC, 0.71 [0.63, 0.80] vs 0.68 [0.61, 0.79], p=0.34) or children (0.72 [0.63-0.81] vs. 0.79 [0.70-0.87], p=0.42). CONCLUSION: Decrease in serum K18 levels is strongly associated with improvement in liver histology in adults or children with NAFLD. However, K18 decrease did not perform better than ALT improvement in identifying histological changes in NAFLD.